Pertinence of Environmental Accounting for contribute to the sustainability of environmental wealth - Ceballos Rincón, Olga Inés (2020)
Objective: To analyze the knowledge and acceptance that the accounting academic community has regarding the development and structure of biocontability, understood as the emerging discipline that tends to contribute to the sustainability of the environmental wealth. Method: The develop research is descriptive and inductive, so far as it identifies through a sample the position of accounting experts regarding the environmental accounting and biocontability pertinence to represent natural wealth in function to the sustainability of it. Results: The study allows to know that the accounting academic community Has advanced in accepting the need to develop a structure for this discipline that allows the preparation and presentation of information on environmental wealth, through a different model as the financial-accounting. Conclusions: it concludes that an environmental accounting system must have recognition criteria, assessments methods, information to present and revealing the own natural dimension to inform and yield accounts regarding to its study objective.